Seeking unique dogs: The increase in individualism in Japan - Yuji Ogihara; Yukiko Uchida (Acta Psychologica)
Previous research indicated that Japanese culture came to increasingly emphasize uniqueness, showing a rise in individualism. However, such research focused on the naming of babies, making it unclear whether this trend was found in other behaviors. Therefore, the current research examined temporal changes in the behavior of choosing dog types. Study 1 confirmed that choosing hybrid dogs (mixed-breed dogs created by crossing purebred dogs) as a form of uniqueness-seeking was shared in Japanese culture. Study 2 indicated that the ownership rates of unique hybrid dogs increased and the ownership rates of common purebred dogs decreased between 2008 and 2017. Study 3 showed that people increasingly sought information about hybrid dogs online between 2004 and 2018. Study 4 demonstrated that articles in newspapers referring to hybrid dogs increased between 2003 and 2018. These results consistently suggest that people in Japan came to seek more uniqueness and Japanese culture became more individualistic.